2017
DOI: 10.2989/20702620.2017.1318347
|View full text |Cite
|
Sign up to set email alerts
|

First record ofQuadrastichus mendeli, a parasitoid ofLeptocybe invasa, in South Africa

Abstract: Leptocybe invasa, the blue gum chalcid, is a well-known pest of Eucalyptus. Since it was first noticed in the Mediterranean and Middle East in 2000, it has spread to other Eucalyptus growing countries around the world. Efforts to control it have included the release of a number of larval and pupal parasitoids. This Report Note serves as the first record of the presence of Quadrastichus mendeli in South Africa, a parasitoid originally released as a biological control agent of L. invasa in Israel. The interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…It prefers to parasitize young and mature larvae of L. invasa , with a percentage of parasitism at 84.20±11.40 (Kim et al, 2008; Zheng et al, 2017). Q. mendeli is now successfully established in Australia, China, Cambodia, India, Israel, Italy, Kenya, Laos, South Africa, Thailand, and Vietnam (Lawson et al, 2014; Mendel et al, 2017; Bush et al, 2018), and it effectively controls L. invasa populations in the field (Kim et al, 2008). Q. mendeli is likely to have existed in many other countries worldwide but has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It prefers to parasitize young and mature larvae of L. invasa , with a percentage of parasitism at 84.20±11.40 (Kim et al, 2008; Zheng et al, 2017). Q. mendeli is now successfully established in Australia, China, Cambodia, India, Israel, Italy, Kenya, Laos, South Africa, Thailand, and Vietnam (Lawson et al, 2014; Mendel et al, 2017; Bush et al, 2018), and it effectively controls L. invasa populations in the field (Kim et al, 2008). Q. mendeli is likely to have existed in many other countries worldwide but has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because the name M. zvimendeli has been cited in publications regarding the species' use in biocontrol (Dittrich-Schröder et al ., 2014; Bush et al ., 2017; Mendel et al ., 2017), precedence was given to M. zvimendeli Doğanlar and Hassan 2013 (the Principle of the First Reviser, Article 24.2, ICZN Code). Megastigmus judikingae Doğanlar and Hassan 2010 becomes a junior synonym.…”
Section: Resultsmentioning
confidence: 99%
“…Because the name M. zvimendeli has been cited in publications regarding the species' use in biocontrol (Dittrich-Schröder et al, 2014;Bush et al, 2017;Mendel et al, 2017) Megastigmus sichuanensis Doğanlar & Zheng was described in 2017 (Doğanlar et al, 2017;Huang et al, 2017). Nuclear 28S DNA and mitochondrial COI DNA sequences obtained from specimens provided by our colleagues in China fully matched M. zvimendeli ( fig.…”
mentioning
confidence: 93%
“…Female Q. mendeli prefers to parasitize young and mature larvae of L. invasa with a percentage of parasitism of 84.20 ± 11.40 23 . Q. mendeli has now been successfully established and effectively controls L. invasa populations in elds in Australia, China, Cambodia, India, Israel, Italy, Kenya, Laos, South Africa, Thailand and Vietnam [25][26][27][28][29] . Previous studies revealed that sensory genes of parasitoids play important roles in locating hosts 8 .…”
Section: Introductionmentioning
confidence: 99%